Analisis kinerja dan studi kelayakan penerapan alat pemberi isyarat lalu lintas pada simpang tiga tak bersinyal Betro - Derry Risqullah Putra; Nurani Hartatik (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
This study was motivated by the high volume of traffic passing through the intersection of Jalan Garuda - Jalan Rajawali - Jalan Raya Betro, which has the potential to cause congestion and reduce the performance of the intersection. The objectives of the study were to analyze the highest number of vehicles crossing the intersection each day, evaluate the performance of the intersection when given a traffic signal (APILL), and determine the appropriate alternative improvements to reduce congestion at that location. The method used is the Pedoman Kapasitas Jalan Indonesia manual (PKJI) 2023 to measure capacity (C), degree of saturation (DJ), delay (T), and queue opportunitie (PA). The results of the analysis show that the highest traffic volume occurred on Thursday, February 20, 2025, at 15:00-16:00 WIB with a total of 2,016 smp/hour, resulting in a capacity (C) of 2,209 smp/hour with a degree of saturation (DJ) of 0.91 and a delay (T) 16 seconds/hour and queue opportunitie (PA) upper limits at 66% and lower limit at 33% so that the level of service (LOS) is in category E, which means unstable motion, stalled vehicles. Then after applying the APILL signal it is estimated that it can increase the capacity (C) 3520 smp/hour, with the degree of saturation (DJ) being 0.75, and the average delay (T) decreasing to 7.52 seconds/hour, and shortening the queue length (PA) to 33 meters so that the level of service (LOS) is in category D. The contribution of this research is to provide valid and data-driven recommendations for intersec